2014
DOI: 10.4161/derm.29799
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence for vitamin D deficiency in nodulocystic acne

Abstract: Objective: Acne vulgaris is a chronic inflammatory disease, and hormonal influences, follicular plugging and follicular hyperkeratinization, increased sebum secretion, Propionibacterium acnes colonization, and inflammation are involved in its pathogenesis. Recently, a significant body of evidence has accumulated that describes the comedolytic properties of vitamin D and its roles as a modulator of the immune system, a regulator of the proliferation and differentiation of sebocytes and keratinocytes, and as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 34 publications
(37 reference statements)
6
40
1
1
Order By: Relevance
“…Serum level of 25 hydroxy vitamin D was found to be inversely related with acne severity suggesting that there is a connection between low vitamin D and acne. This is in agreement with a previous study which found a decrease in the levels of 25 hydroxy vitamin D in patients with nodulocystic acne than that in the control group . Also, Lim et al found a significant lower vitamin D level in patients with acne than normal subjects.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Serum level of 25 hydroxy vitamin D was found to be inversely related with acne severity suggesting that there is a connection between low vitamin D and acne. This is in agreement with a previous study which found a decrease in the levels of 25 hydroxy vitamin D in patients with nodulocystic acne than that in the control group . Also, Lim et al found a significant lower vitamin D level in patients with acne than normal subjects.…”
Section: Discussionsupporting
confidence: 92%
“…Acne vulgaris is a multifactorial chronic inflammatory disorder of the pilosebaceous follicles of human skin . Acne vulgaris can persist throughout life and may cause permanent scarring on the face.…”
Section: Discussionmentioning
confidence: 99%
“…They also observed no correlation between the severity of acne and vitamin D level. Another study conducted with 43 patients with acne found that the vitamin D level was lower in patients with acne (14).…”
Section: Discussionmentioning
confidence: 99%
“…As an antioxidant, vitamin D may contribute to the development of acne (13,14). Some authorities think that vitamin D influences the activities of superoxide dismutase(SOD) and glutathione peroxidase (GSH-Px), which are found in the papulopustular acne (15).…”
Section: Discussionmentioning
confidence: 99%
“…Sebocytes and keratinocytes both are considered as 1,25(OH)2D3‐responsive cells . VitD regulates the proliferation and differentiation of keratinocytes and suppresses sebum secretion .…”
Section: Introductionmentioning
confidence: 99%